2012
DOI: 10.15241/eht.1.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Counselor-in-Training Perceptions of Supervision Practices Related to Self-Care and Burnout

Abstract: Counselors-in-training face the challenges of balancing academic, professional, and personal obligations. Many counselors-in-training, however, report a lack of instruction regarding personal wellness and prevention of personal counselor burnout. The present study used CQR methodology with 14 counseling graduate students to investigate counselor-in-training perceptions of self-care, burnout, and supervision practices related to promoting counselor resilience. The majority of participants in this study perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 16 publications
1
26
0
2
Order By: Relevance
“…For example, faculty supervisors could add a role to Borders’s (1991) peer group supervision model that asks CITs to listen for overinvolvement with client experiences while listening to client tapes during group supervision seminars. Moreover, research shows that topics related to CIT self‐care are rarely addressed in on‐site supervision (Thompson, Frick, & Trice‐Black, 2011). It is important for on‐site supervisors to monitor personal distress in CITs and engage in discussions related to how to manage the personal discomfort that arises from difficult client circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…For example, faculty supervisors could add a role to Borders’s (1991) peer group supervision model that asks CITs to listen for overinvolvement with client experiences while listening to client tapes during group supervision seminars. Moreover, research shows that topics related to CIT self‐care are rarely addressed in on‐site supervision (Thompson, Frick, & Trice‐Black, 2011). It is important for on‐site supervisors to monitor personal distress in CITs and engage in discussions related to how to manage the personal discomfort that arises from difficult client circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical sequence (e.g., practicum, internship) appears to be a logical place to address burnout prevention and wellness with students because it is their first exposure to clients and potential work stressors (Lambie, ). In a qualitative study of CITs enrolled in either practicum or internship, Thompson, Frick, and Trice‐Black () found that participants believed that they experienced some level of burnout and desired more feedback from their supervisors about work–life balance.…”
Section: Wellnessmentioning
confidence: 99%
“…Thompson, Frick, and Trice‐Black () suggested that CITs desire supervisory support about strategies for work–life balance. However, there are currently only a few empirical studies demonstrating causal relationships between wellness‐based supervisory interventions and their related effects on CIT wellness (Lenz, Sangganjanavanich, Balkin, Oliver, & Smith, ; Meany‐Walen, Davis‐George, & Lindo, ; Storlie & Smith, ).…”
Section: Welms For Promoting Skills Development and Personal Wellnessmentioning
confidence: 99%